(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Cervical cancer (CC) is caused by the Human Papillomavirus (HPV) and can be defined as the uncontrolled multiplication of the cells of the uterine epithelium, potentially compromising underlying tissues such as organs and other structures. Objective: To describe the epidemiological profile and lesion staging of women affected by cervical cancer in Maranhão. Methods: Descriptive, cross-sectional study using secondary data from the Hospital Cancer Registry Health Information System, from January 1 to December 31, 2022. Results: Of the 464 women diagnosed with cervical cancer, there was a predominance of the 33–47 age group. Regarding origin, the highest prevalence was found in the state capital, São Luís, Maranhão, with 161 records (34.70%). As for the staging of cervical cancer lesions, the highest number was found at stage IIIB, with 103 records (22.20%). Conclusion: The findings show that, in the referral unit studied, women were predominantly diagnosed at advanced stages of the disease, especially at stage IIIB. These results highlight weaknesses in screening, early detection, and timely access to health services, reinforcing the urgent need to strengthen public policies aimed at expanding cytological screening coverage and broadening access to primary care services.